The Effectiveness of Biscuit Consumption of Pregnant Women on Increasing the Circumference of The Upper Arm in Pregnant Women With Chronic Energy Deficiency (CED) in the Karawang Kulon Health Center Area - Jayanti, Putri Noer; Nofa Anggraini (STIKep PPNI Jawa Barat, 2022)
Aims: This study aims to determine the effectiveness of the supplementary feeding program for CED pregnant women in the Karawang Kulon Health Center Working Area. Methods: Pre-experimental research with a design of one group pretest-posttest design, and the statistical test is testing T. Number of samples = 20 respondents, data collection by observation before and after being given biscuits for pregnant women in the Karawang Kulon Health Center area. Results: The upper arm circumference condition in 20 respondents of pregnant women after being given biscuits showed a Chronic Energy Deficiency (CED) value of the upper arm circumference <23.5 by 3 respondents. Meanwhile, the CED value was ≥ 23.5 for 17 respondents. In addition, the Wilcoxon Singed Rank Test results showed an effect of giving biscuits on CED pregnant women (p-value 0.000). Conclusion: The need for guidance from the government and the surrounding environment regarding the importance of nutritious food to pregnant women so that the baby grows up healthy.